2004
DOI: 10.1111/j.1365-2125.2004.02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous indometacin in preterm infants with symptomatic patent ductus arteriosus. A population pharmacokinetic study

Abstract: AimsTo characterize the population pharmacokinetics of indometacin in preterm infants with symptomatic patent ductus arteriosus and to investigate the influence of various factors on the response to treatment. MethodsData were collected from 35 infants (gestational age 25-34 weeks; postnatal age 1-77 days) in neonatal units in Belfast and Copenhagen. Infants received an initial course of up to three doses of intravenous indometacin (0.1-0.2 mg kg -1 ) as considered appropriate by the treating physician. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
1
27
0
3
Order By: Relevance
“…Ibuprofen clearance increases from 2.06 mL/h/kg at 22-31 weeks PCA [20], 9.49 mL/h/kg at 28 weeks PCA [21] to 140 mL/h/kg at 5 years [22]. Similar maturation is now reported for indometacin [23]. The volume of distribution is increased in neonates compared with older children and adults.…”
Section: Pharmacokineticssupporting
confidence: 68%
“…Ibuprofen clearance increases from 2.06 mL/h/kg at 22-31 weeks PCA [20], 9.49 mL/h/kg at 28 weeks PCA [21] to 140 mL/h/kg at 5 years [22]. Similar maturation is now reported for indometacin [23]. The volume of distribution is increased in neonates compared with older children and adults.…”
Section: Pharmacokineticssupporting
confidence: 68%
“…Shaffer et al concluded that indomethacin clearance is solely due to individual pharmacokinetic differences regardless of weight (5). Smyth et al also reported high interindividual variability, although indomethacin metabolism did vary by weight (6). Validation studies to demonstrate the value of these polymorphisms in predicting response to indomethacin should be performed and translated into clinical practice to reduce the morbidity associated with prolonged PDA and indomethacin toxicity where indomethacin treatment is likely to be futile.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, post-treatment plasma concentrations and inter-patient pharmacokinetic differences have been shown to affect closure rates. Pharmacokinetic studies demonstrate considerable variability in indomethacin clearing among preterm infants with PDA (5, 6). Furthermore, PDA requiring indomethacin therapy has been reported as highly heritable, as has failure to respond to indomethacin therapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…Most immature infants are likely to require pharmaceutical treatment to close the ductus, thereby avoiding the need for PDA ligation (10,11). Pharmaceutical treatment enables doctors to cope with more patients and save operation costs for infants (12,13).…”
Section: Introductionmentioning
confidence: 99%